Importance of country factors for global differences in audit pricing: New empirical evidence - Brigitte Eierle; Sven Hartlieb; David C. Hay; Lasse Niemi; Hannu Ojala (International Journal of Auditing, 2021)
In recent years, we have seen an increasing interest in the country-level differences in audit environments as they might have a pervasive impact on how financial statement audits are conducted around the world. We contribute to this emerging stream of research in three important ways. Firstly, we provide a comprehensive synthesis of country-level determinants that have been employed in previous multinational auditing research. Secondly, we document economically significant differences in the overall levels of audit pricing between countries, which we interpret as a compelling evidence that audits are conducted differently in different countries. Lastly, we explain these pricing differences between countries with a large set of country variables identified in our synthesis of prior multinational auditing research. We find not only that economic and regulatory characteristics explain the most of the differences in audit pricing between countries but also that differences attributable to sociological characteristics seem to be important in the conduct of audits. As auditing as a service and profession has become increasingly globalized, our study should be of interest to a wide range of readers including researchers, practitioners and regulators.
Keywords: 650; audit fees; auditing; country characteristics; cross-country research